Remote Sensing Applications in Tidal Current Hotspot Mapping (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The Mearim River region, located in the state of Maranhão, Brazil, offers geographic and climatic conditions favorable for the exploration of marine renewable energies, such as wind, solar, and tidal power. This region has an extensive coastline, significant solar irradiation, constant winds, and a large tidal range.One of the primary advantages of this area is its proximity to urban centers and electrical infrastructure, including high-voltage transmission lines and substations. This proximity allows for direct connection of power generation to Brazil’s National Interconnected System (SIN).The main objective of this study is to identify hotspots (areas with the highest energy potential within the studied zone) for electricity generation using tidal currents.The proposed methodology combines satellite imagery with the open-source hydrodynamic modeling tool Delft-3D. To achieve this objective, the study was divided into two phases.The first phase involved three campaigns of in situ measurements, each lasting 25 hours and conducted across different tidal cycles and locations. This approach provided greater data variability, including current speed, depth, temperature, salinity, turbidity, and other parameters. Using these data, along with tide tables and regional mapping, hydrodynamic models of the site were generated by Delft-3D.The second phase consisted of acquiring satellite images and processing them. Finally, a correlation is established between the measured real-world data, the generated model, and the satellite images, enabling the identification of hotspots for harnessing tidal currents.Preliminary results show that this is a more economical alternative route, in addition to reducing the time and number of measurement campaigns, and therefore increasing costs, and, at the same time, resulting in detailed information that allows an analysis of the selected areas in a short period of time.